Lake Victoria’s bounty: A case for riparian countries’ blue economic investment - Nyamweya, C. S.; Nyaboke, H. M.; Aura, C. M.; Momanyi, K. N.; Mlaponi, E.; Odoli, C. O.; Njiru, J. M. (Frontiers in Environmental Science, 2022)
People residing in Lake Victoria's basin and riparian countries benefit from ecosystem services provided by the lake. However, the lake's resources, particularly its fish, are under threat from human-caused pressures such as overfishing, alien species invasion, rising eutrophication, and climate change. In this assessment, we look at how to maximize the lake's benefits through product diversification, value addition, and sustainable use of its fisheries. We show that minimizing post-harvest losses of the silver cyprinid (Rastrineobola argentea), locally known as Dagaa, will provide more high-quality fish for human consumption while significantly increasing fishing earnings. Furthermore, by utilizing biowaste (frames, skin, and fish mouth), revenues from Nile perch could be increased up to thrice. Furthermore, if fishing could target Maximum Sustainable Yield(MSY), landings of Nile perch and Dagaa could increase significantly in the long run. These, combined with investments in other areas such as lacustrine tourism and recreation, as well as fish cage culture, can help the Lake Victoria region's blue economy expand.